The Role of Cognitive-Behavioural Therapy for Patients with Depression in Parkinson's Disease - Andreas Charidimou; John Seamons; Caroline Selai; Anette Schrag (Parkinson's Disease)
Depression is a common complication of Parkinson's disease (PD) with considerable impact on patients' quality of life. However, at present the most appropriate treatment approach is unclear. There are limited data on antidepressant medications in PD-associated depression (dPD) and those available suggest limited efficacy and tolerability of these drugs. Cognitive behavioural therapy (CBT) has been shown to be an effective treatment of depressive disorders. Treatment of dPD with CBT may pose particular challenges, including possible different pathophysiology, physical and mental comorbidities, and barriers to treatment through disability, which do not allow simple transfer of these results to patients with dPD. However, a number of case reports, case series, and small pilot studies suggest that this is a promising treatment for patients with PD. We here summarise the published evidence on this treatment in dPD.